EVALUASI KEBIJAKAN UNDANG – UNDANG PERKAWINAN PADA MASYARAKAT SARONGGI, SUMENEP, MADURA - Hamdani, Silfiah; Kusuma Wijayanto, Purbayakti (Solidaritas, 2025)
ABSTRACTEVALUATION OF MARRIAGE LAW POLICY IN SARONGGI COMMUNITY, SUMENEP, MADURAEarly marriage is still a common phenomenon in various regions in Indonesia, including in Saronggi District, Sumenep, Madura. The Marriage Law in Indonesia aims to regulate marriage procedures and provide legal protection for married couples and children. However, its implementation in various regions still faces challenges, especially in areas with strong culture and customs, such as Saronggi, Sumenep, Madura. This study aims to analyze how the Marriage Law is implemented in the Saronggi community, the obstacles faced, and its impact on the rights of women and children. The method used in this study is a qualitative approach with data collection techniques through interviews, observations, and document analysis. The informant determination technique uses purposive sampling and snowball sampling. Data analysis uses Miles and Huberman's interactive analysis. qualitative with interview techniques, observations, and literature studies to obtain relevant data. The results of the study show that the implementation of Law No. 16 of 2019 concerning marriage in Saronggi still faces obstacles. Based on the theory of policy evaluation according to William N. Dunn (2003) with 6 indicators, it was found that the effectiveness of the policy is still low, the efficiency of implementation is also not optimal, the adequacy of the policy is still unable to overcome the root of the problem, the implementation of the policy is also not evenly distributed between urban and rural communities, government responsiveness is still reactive, and the accuracy of the policy is not fully in line with local socio-cultural conditions. In addition, there are forms of conflict between government policies and people's lives, such as the practice of early marriage, forced matchmaking, and polygamy without permission.Keywords: Marriage Law, early marriage, policy implementation.